Jens Rasmussen's risk management framework. (2nd January 2020) - Lintern, Gavan
Abstract: Jens Rasmussen developed a risk management framework that is extensive and multi-faceted. This framework is generally regarded as normative largely because the numerous citations of his work relate to isolated elements of that framework. There are, however, neglected elements to Rasmussen's framework, such as functional-relational modelling, work domain analysis, and development of ecological information systems, that mark it as formative. In this article, I lay out Rasmussen's risk management framework as gleaned from several of his publications. Rather than evaluation, the intent is to describe, and where necessary, explain his ideas. I follow with a review of AcciMap research that has been inspired by Rasmussen's ideas. Based on that review, I conclude that Rasmussen's formative strategy contains ideas that do not have a high profile within our current discourse on risk management. Given the limitations of a normative approach to risk management, coupled with the catastrophic potential of many of our contemporary sociotechnical systems, serious assessment of those neglected aspects of Rasmussen's risk management framework seems warranted.